2014
DOI: 10.1186/s40643-014-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Poly-β-hydroxybutyrate production and management of cardboard industry effluent by new Bacillus sp. NA10

Abstract: Background: In the present study, we aim to utilize the ecological diversity of soil for the isolation and screening for poly β-hydroxybutyrate (PHB)-accumulating bacteria and production of cost-effective bioplastic using cardboard industry effluent. Results: A total of 120 isolates were isolated from different soil samples and a total of 62 isolates showed positive results with Nile blue A staining, a specific dye for PHB granules and 27 isolates produced PHB using cardboard industry effluent. The selected is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 44 publications
(42 reference statements)
1
26
0
Order By: Relevance
“…47) Molecular weight of PHB accumulated in Bacillus sp. under in vitro conditions has been reported to range from 200-500 kDa, 20,48,49) thus the potent isolate B. cereus SE-1 is assumed to accumulate PHB with the same range of molecular weight. However, the slight variation of molecular weight of PHB may not impact negatively on the PHB extraction practices as well as in its further characterization.…”
Section: Discussionmentioning
confidence: 99%
“…47) Molecular weight of PHB accumulated in Bacillus sp. under in vitro conditions has been reported to range from 200-500 kDa, 20,48,49) thus the potent isolate B. cereus SE-1 is assumed to accumulate PHB with the same range of molecular weight. However, the slight variation of molecular weight of PHB may not impact negatively on the PHB extraction practices as well as in its further characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Polyhydroxyalkanoates are macromolecules synthesized by many bacteria, and it is accumulated as intracellular granules to levels as high as 90% of cell dry weight (Reddy et al, 2003). It is stored in those microorganisms under conditions of nutrient stress in the presence of an excess carbon source (Reddy et al, 2009;Bhuwal et al, 2014). It has been demonstrated that Bacillus megaterium is able to produce different kinds of PHA from many feedstocks (including glycerol), such as poly(3HB-co-3HV) and PHB (Moreno et al, 2015;Porras et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates are a natural resource commonly available as lignocellulosic biomass that can be hydrolyzed into sugars to be further converted via fermentative or thermochemical processes into useful products (Zhang 2008;Arora et al 2015). Among the important products that can be derived are ethanol (cellulosic), butanol and similar advanced fuels, platform chemicals such as acetone, furfural, levulinic acid, gamma valerolactone and bioplastics such as polyhydroxy butyrates or valerates (Zhang 2008;Singh et al 2008;Galbe and Zacchi 2002;Bhuwal et al 2014). These products are a substitute for fossil fuels or starch-based carbohydrates, thus providing an alternate sustainable resource.…”
Section: Introductionmentioning
confidence: 99%
“…However, direct hydrolysis of the cellulose into sugars can be particularly attractive due to the simplicity of the process and ready use of the sugar solution after concentration (Wang et al 2012). These sugars can be used as a feedstock for conversions into biofuels and bioplastics such as polyhydroxy alkanoates or into platform chemicals such as succinic acid, lactic acid, levulinic acid and furfurals (Zhang 2008;Bhuwal et al 2014;Graf and Koehler 2000;Lark et al 1997;Kádár et al 2004) Of the varieties of paper mill fines rejects, those from recycled pulp mills using old corrugated cartons are particularly important. Some modern OCC mills find that rejecting 'inactive' fines into the waste stream can be more profitable than using them in the manufactured product, particularly recycled linerboard.…”
Section: Introductionmentioning
confidence: 99%